Numerical analysis on the performance of Dual Rotor wind turbine (International Journal of Scientific Research and Management (IJSRM), 2020)
This study investigates the aerodynamic performance of wind turbines aiming to maximize the power extracted from the wind. The study is focusing on the effect of introducing a second rotor to the main rotor of the wind turbine in what is called a dual rotor wind turbine (DRWT). The numerical study took place on the performance of small-scale model of wind turbine of 0.9 m diameter using S826 airfoil. Both the Co-rotating and Counter rotating configurations were investigated at different tip speed ratios (TSR) and compared with the performance of the single rotor wind turbine (SRWT). Many parameters were studied for dual rotor turbines. These include the spacing between the two rotors, the pitch angle of the rear rotor and the rotational speed of ratio rear to front rotor. Three-dimensional simulations performed and employed using CFD simulations with Multi Reference Frame (MRF) technique. The Co Rotating Wind Turbine (CWT) and Counter Rotating Wind Turbine (CRWT) found to have better performance compared to that of the SRWT with an increase ranging from 12 to 14% in peak power coefficient. Moreover, the effect of changing the pitch angle of the rear rotor on the overall performance found to be of a negligible effect between angles 0⁰ until 2⁰ degrees tilting toward the front rotor. On the other hand, the ratio of rotational speed of the rear rotor to the front rotor found to cause a further increase in the peak performance of the CWT and CRWT ranging from 3 to 5%.